Implementation of Think, Talk, Write Strategy in Improving Studens’ Learning Activity at Learning PAI in SMP Al-Islah Center Gunung Anyar Surabaya - Siti Shofiyah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
To create creative, fun learning in need of various teaching skill or teaching skill, this research problems are formulated: first, how to apply Think, Talk, Write (TTW) Learning Strategy in PAI learning at SMP Al-Islah at Central Gunung Anyar of Surabaya?; second, how to increase students' activity on learning PAI at SMP Al-Islah at Central Gunung Anyar Surabaya?           In this research, researchers used descriptive qualitative research. The data collection technique used observation, documentation and interview, while the data analysis used inductive, deductive and comparative method.           Based on the research results, it can be concluded: First, Think, Talk, Write Strategy applied in SMP Al-Islah at Central Gunung Anyar Surabaya by forming groups that each must be able to present the content of the verse, reading by tajwid in the verse . Each group should be active in this activity because the students' scores can be obtained from the points given by teachers during discussion and question and answer. The implementation of this strategy does not experience significant problems or constraints, Think, Talk, Write strategy has given very satisfactory results, in addition, this strategy also used several methods such as lectures, Questions and answers, etc. In the learning process; Second, using the Think, Talk, Write strategy can be said that the students' learning activity is good, because the children have fulfilled some of the liveliness indicators of learning, more enthusiastic and more excited. Keywords: Think, Talk, Write Strategy, Students’ Learning Activity, and Implementation.